(Em defesa dos) Cuidados Paliativos na Atenção Primária à Saúde - Combinato, Denise Stefanoni; Ferreira Martins, Sueli Terezinha [UNESP] (My University, 2012)
One of the basic principles of the Brazilian Public Health System (SUS) is integral assistance, which considers the integrality of the individual, of service and care, which should necessarily include end of life care. Our aim was to analyze the work process of health professionals at the Family Health Strategy / Primary Care that already cared for people in the dying process to propose viable contributions to the Public Health area as regards the implementation of Palliative Care in Primary Care. We present data referring to the following themes: Singular Therapeutic Project (PTS); death quality as PTS goal (work purpose); the team's ways of doing (bonding as a pact condition). Eleven health professionals (four nurses and seven physicians) linked to the Family Health Strategy (ESF) of Campinas (São Paulo) participated on this research. From the interviews, data analysis followed the Socio-Historical Psychology theoretical and methodological approach. The professionals' activity was analyzed in articulation with the specificities of caring for people in the dying process. We found that action planning in health is oriented by the Singular Therapeutic Project (PTS), with an emphasis in social diagnosis and the need of a bond for attaining a pact. It is understood that the purpose of health professionals' activity is to promote dignity and life quality in the dying process, but integral care should include not only individual and family care, but also the defence of full human development during all phases of life.
(Pleading for) palliative care in primary health care
Keywords: Family Health; Hospice Care; Primary Health Care; Psychology; Public Health.